Comparison of biochemical and immunological profile of pediatric patients with acute myeloid leukemia in relation to healthy individuals - Fabiane L.F.Z. Sanches; Taís M. Nitsch; Maria Marluce S. Vilela; Valdemiro C. Sgarbieri (Elsevier, 2015)
ABSTRACT OBJECTIVE: To compare the biochemical and immunological profiles of pediatric patients with acute myeloid leukemia (AML) with healthy children and adolescents. METHODS: This was a cross-sectional study in which 21 therapy-naïve patients with AML were compared with a group of 24 healthy individuals. The following data were analyzed: serum proteins, leucocytes and subgroups, erythrocytes, hematocrit, hemoglobin, platelets, cytokines in peripheral blood mononuclear cells cultures under spontaneous and BCG- or PHA-stimulated conditions, immunoglobulin A, and erythrocytic glutathione. Statistical analysis was performed using SPSS software, considering as significant p-values < 0.05. RESULTS: Serum albumin levels were higher (p < 0.0001) in the control group, as well as all the parameters related to red blood cells (p < 0.0001). For leucocytes and subgroups, no statistical difference was found between the AML and the control groups. For cytokines, the concentrations were significantly higher under spontaneous and BCG-stimulated conditions for TNF-a, IL-6, IL-10, and IFN-? in the control group. Under PHA-stimulated conditions, the concentration was higher (p = 0.002) only for IL-6. No difference was found between the two groups for the other cytokines and for IgA in the saliva. Erythrocytic glutathione was higher (p < 0.0001) in AML patients. CONCLUSIONS: It was possible to characterize the biochemical and immunological profile of pediatric patients with AML, as well as highlight some significant differences in these parameters when comparing with healthy children and adolescents.